ANALYZING GENSHIN IMPACT PLAYER BEHAVIOR FOR STRATEGIC DEVELOPMENT IN THE GAMING INDUSTRY - Rochelle, Jessenia Nadea; Rumokoy, Lawren Julio; Gunawan, Emilia Margareth (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyse the online game player of Genshin Impact, one of the popular cross platforms online games and to analyse also a strategic development for gaming industry based on the player behaviour. The variable in this study is Consumer Behaviour. This research uses a qualitative method with a sample of 15 Genshin Impact players in Manado that already played the game for minimum 2 months. Data was collected through face to face in depth interview. The results of this study indicate that based on player’s preference, enjoyment and satisfaction can build a certain behaviour when playing the game also have an impact to player’s long term gaming engagement. A company also can make a strategy based on player’s preference, enjoyment and satisfaction so the player may stay to play the game for a long term of time.   Keywords: Consumer Behaviour